Numerical simulation of endoscopic magnetoacoustic tomography with magnetic induction. (1st November 2017) - Zheng, Sun; Zhen, Ma
Abstract: Endoscopic magnetoacoustic tomography with magnetic induction (EMAT-MI) provides an interventional tool to detect the electrical conductivity distribution of a tubular structure with high spatial resolution. In this work, a preliminary study on the numerical simulation of EMAT-MI images was conducted. The magnetic excitation, generation and propagation of magnetoacoustic (MA) waves in the multi-layered wall tissues were modeled and numerically simulated. The cross-sectional distribution of the acoustic source and electrical conductivity was recovered from the acoustic pressure series based on time-reversal. The validity has been demonstrated on two computer-generated phantoms. Results suggested that the conductivity boundaries can be clearly distinguished in the images of acoustic-source or conductivity distribution which are highly consistent with the numerical simulation. The resolution of the MA signals excited by the Lorentz force divergence is closely related to the pulse width of the excitation current. Sparse measuring locations and limited-view scanning may reduce the image quality although higher SNR of the MA signals leads to better image reconstruction.